The roles of financial knowledge, government support, and social networking on financial resilience among women SMEs in Malaysia - Mahadi, Nur Farhah; Yusuf, Muhammad-Bashir Owolabi; batubara, maryam; Kamal Azhar, Siti Mardhiyah (2025)
Purpose and background: Global businesses, particularly small and medium-sized organizations (SMEs), are facing currently unheard-of difficulties as a result of the COVID-19 epidemic. Women entrepreneurs in Malaysian SMEs face unique hurdles that impede their pursuit of financial resilience during these uncertain times. This study examines the impact of financial knowledge, government support, and social networking on the financial resilience of women in SMEs in Malaysia amidst the ongoing COVID-19 pandemic. Methods: Structural equation modeling (SEM) is employed to analyze the relationships between these factors. To conduct the analysis, exploratory factor analysis (EFA) is performed using the SPSS 20 package, while SmartPLS is utilized for measuring the structural equation models. Results/findings: The results reveal statistically significant and positive relationships between financial knowledge, government support, social networking, and financial resilience. Higher levels of financial knowledge, government support, and social networking are associated with increased levels of financial resilience. Conclusions/ implications: The study concludes by highlighting the important contributions that social networking, government assistance, and financial knowledge made to strengthen the financial resilience of women-led SMEs in Malaysia during the COVID-19 epidemic. These elements support women entrepreneurs' enhanced performance and greater levels of pleasure while also having a favorable impact on their financial resiliency. These results lead to the following suggestions being put forth: Encouraging Social Media Presence: Platforms and networks that encourage social networking among female entrepreneurs should be developed. Women may develop important social networks, access resources, and get assistance when they need it most when they are given chances for cooperation, knowledge exchange, mentorship, and peer support. Online groups, networking events, and industry-specific forums may all help women-led SMEs build stronger social networks.